A pauta racial nas empresas brasileiras e as experiências raciais de trabalhadores/as negros/as do setor de tecnologia da informação e comunicação - Ribeiro, Denise Santos (2023)
In this master’s research, we aim to understand how the “racial agenda” has been mobilized by Brazilian companies, especially from the repercussions of the murder of George Floyd, and how black informational/digital workers experience insertion and permanence in a markedly white sector, which, to a greater or lesser extent, have sought to incorporate this “agenda”. To this end, we followed cases of companies that had public repercussions on the national scene, either through statements considered racist or selection processes exclusive to black professionals. We work with the Nubank, Magazine Luiza, and Ável repercussions. Aligned with this larger context, we sought to understand the perceptions of black informational workers who work in technology companies in the city of São Carlos-SP. We used the life history method to access black employees’ perceptions and racial experiences in different stages of their lives, focusing on their racial experience in the current work. Based on the interviews, we sought to understand whether and in what ways these workers would be targets of racial distinction. We noticed that their organization in a collective or committee allows important deliberations for this group and its permanence within the company. This ambiguous position these workers occupy in the company does not escape the logic of exploitation, since they become the main ones responsible for combating the inequalities that cross them through the creation of actions of diversity and inclusion, and the racial literacy of the other workers, without the due financial return. Finally, we try to discuss through the literature how the concepts of diversity, identity, and difference are understood in this context.